Effect of the branching pattern of hydrophobic dendrons on the core structure of linear-dendritic copolymer micelles - Kalva, Nagendra; Aswal, Vinod K.; Ambade, Ashootosh V. (Macromolecular Chemistry and Physics, 2014)
Hydrophobic dendrons based on different branching patterns, viz. 3,5-di- and 3,4,5-trisubstituted phenyl rings, consist of the same backbone but exhibit different sizes, shapes, and hydrophobic densities. These dendrons are attached to poly(ethylene glycol) and the core properties of the copolymer micelles are investigated in tetrahydrofuran (THF)/water mixtures by neutron scattering. Two polymers with intermediate hydrophobicity are studied further with variations in the solvent composition and the temperature. The aggregation numbers for 3,4,5-based dendron copolymers are lower, with more THF molecules of solvation compared with the 3,5-based dendron copolymer, the difference being greater at higher generations due to different molecular shapes. The micellar core size increases in small steps with dendron size so that dye encapsulation is tuned.
Keywords: diblock copolymers; linear-dendritic copolymers; micelles; neutron scattering; structure-property relations